SSCP systems security certified practitioner practice exams - Mitropoulos, Nick (McGraw-Hill, 2019)
Publisher's Note: Products purchased from Third Party sellers are not guaranteed by the publisher for quality, authenticity, or access to any online entitlements included with the product. Hundreds of accurate practice questions and in-depth answer explanations to use in preparation for the SSCP exam This highly effective self-study guide covers all seven domains of the Systems Security Certified Practitioner (SSCP) exam as developed by the International Information Systems Security Certification Consortium (ISC)2®, including updated exam objectives effective November 1, 2018. To reinforce important skills and facilitate retention, every question is accompanied by explanations for both correct and incorrect answers. Designed to help you pass the test with ease, this book is also an ideal companion to the bestselling SSCP® Systems Security Certified Practitioner All-in-One Exam Guide, Third Edition Covers all seven exam domains: " ccess Controls " ecurity Operations and Administration " isk Identification, Monitoring, and Analysis " ncident Response and Recovery " ryptography " etwork and Communications Security " ystems and Application Security Online content includes: " 50 practice questions " est engine that provides full-length practice exams and customized quizzes by chapter or exam domain